Automation in tree fruit production principles and practice - Zhang, Qin, 1956- (CABI, 2017)
This book on automation in tree fruit production consists of 11 chapters covering the following topics: (1) concept of tree fruit production automation; (2) economics of perennial crops production automation; (3) sensing for stress detection and high-throughput phenotyping in precision horticulture; (4) light interception and canopy sensing for tree fruit canopy management; (5) precision orchard systems; (6) variable rate irrigation on centre pivots; (7) precision technologies for pest and disease management; (8) precision nutrient management; (9) precise crop load management; (10) mechanical harvest and in-field handling of tree fruit crops; and (11) opportunity of robotics in precision horticulture.